PERIODONTAL DISEASE AND NOSOCOMIAL PNEUMONIA: A SYSTEMATIC REVIEW - Hanifa Salma, Yasmin (Fakultas Kedokteran Gigi Unjani, 2024)
This study aims to comprehensively review the literature and assess periodontal disease as a risk factor for nosocomial pneumonia in hospitalized patients, particularly those receiving treatment in the intensive care unit (ICU). Case-control studies and